Aktivitas Enzim Peroksidase Daun Planlet Pisang Ketan (Musa paradisiaca L.) Hasil Pengimbasan Ketahanan terhadap Asam Salisilat secara In Vitro - Muslimah, Imamah; Nurcahyani, Endang; Zulkifli, Zulkifli (Politeknik Negeri Lampung., 2017)
Banana plant production are decreased because it getting an attack from Fusarium oxysporum. ?ketan? Banana plantlet that resistant to the Fusarium oxysporum were selected by in vitro in the solid Murashige and Skoog (MS) medium with added salicylic acid at 40 ppm, 50 ppm, 60 ppm, and 70 ppm concentration, compared with controls (0 ppm). The aim of this research is to determine the activity of peroxidase enzyme on leaves of banana ketan plantlet. The research was carried out in December 2015 to February 2016 in the Laboratory of Botani (in vitro room), Departement of Biology, Faculty of MIPA, Lampung University. This study used a completely randomized design with 5 replications. Data were analyzed with the variance (Anova) and if them different will be continued by LSD test performed at 5% significance level. Extraction of peroxidase method using Saravanan et al. (2004) with the mixture of pyrogallol and ?2?2. The absorbance was measured with a spectrophotometer (Shimudzu UV 800) at wavelength (?) of 420 nm and readable from zero. The result showed that the activity of peroxidase enzyme on the leaves banana ketan plantlet has increased optimally in the salicylic acid concentration of 50 ppm compared with controls. Increased of Peroxidase enzyme activity showed that banana ketan plantlet was resistant to the salicylic acid and expected to be resistant to Fusarium oxysporum. Keywords: Salicylic acid, Peroxidase enzyme, Fusarium oxysporum, in vitro, Banana ketan